2012
DOI: 10.1016/j.rie.2012.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Corruption and positive selection in privatization

Abstract: a b s t r a c tWe consider the supply of a public good based on a publicly owned facility. The Government has a choice between provision in-house and privatizing the facility and then outsourcing the production. In particular, we focus on corruption in the decision to privatize and on its effect on social welfare when there is asymmetric information on the public and private manager's efficiency. Our analysis shows that a corrupt Government, that chooses to privatize only in exchange for a bribe, makes a posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Similarly, Rose-Ackerman ( 2007) suggests that the level and incidence of corruption in private sectors were positively associated with a firm's contact with the public sector for such matters as foreign trade, tax collection and regulatory compliance. Meanwhile, Buia and Molinari (2012) suggest that the privatization process is an opportunity for public servants to obtain bribes where the corporation can pay off officials to decide whether to sell state-owned enterprises at what price and to whom. Correspondingly, Bjorvatn and Søreide (2005) state that corruption may be a particularly severe problem in the sale of public assets because it is typically complicated to value these assets.…”
Section: Corruption In the Private Sectormentioning
confidence: 99%
“…Similarly, Rose-Ackerman ( 2007) suggests that the level and incidence of corruption in private sectors were positively associated with a firm's contact with the public sector for such matters as foreign trade, tax collection and regulatory compliance. Meanwhile, Buia and Molinari (2012) suggest that the privatization process is an opportunity for public servants to obtain bribes where the corporation can pay off officials to decide whether to sell state-owned enterprises at what price and to whom. Correspondingly, Bjorvatn and Søreide (2005) state that corruption may be a particularly severe problem in the sale of public assets because it is typically complicated to value these assets.…”
Section: Corruption In the Private Sectormentioning
confidence: 99%
“…The effect of corruption for public welfare has always been an interesting theme for economists (Bardhan, 1997;Jain, 2001). Corruption positively increases agglomeration of industries in India, and has a favorable effect for private firms only when the efficiency of private players is higher than that of the average public bureaucrat (Buia & Molinari, 2012). Other studies showed that India generally has a moderate to large problem with corruption as a whole country (Quah, 2008).…”
Section: Hypothesis H6 Corruption and Lawmentioning
confidence: 99%
“…In particular, the Government, by setting T, can indirectly make a (positive) selection on the type of private manager even if he cannot observe the value of σ P : since less efficient private managers are less willing to pay to get the facility, any strictly positive transfer will exclude less efficient managers (Buia and Molinari 2012).…”
Section: Asymmetric Information and The Selection Effect Of Pricesmentioning
confidence: 99%